Efficient O‐Acylation of Alcohols and Phenol Using Cp2TiCl as a Reaction Promoter. Issue 21 (4th July 2016) - Durán‐Peña, María Jesús; Botubol‐Ares, José Manuel; Hanson, James R.; Hernández‐Galán, Rosario; Collado, Isidro G.
Abstract : A method has been developed for the conversion of primary, secondary, and tertiary alcohols, and phenol, into the corresponding esters at room temperature. The method uses a titanium(III) species generated from a substoichiometric amount of titanocene dichloride together with manganese(0) as a reductant, as well as methylene diiodide. It involves a transesterification from an ethyl ester, or a reaction with an acyl chloride. A radical mechanism is proposed for these transformations. Abstract : A set of primary, secondary, and tertiary alcohols, and phenol, have been converted into the corresponding esters using a substoichiometric amount of bis(cyclopentadienyl)titanium(III) chloride in good yields and under mild reaction conditions.